Contaminação por mercúrio em sedimento e em moluscos do Pantanal, Mato Grosso, Brasil - Vieira, Luiz M. (1995)
The total level of mercury detected in the sediment and in the tissues of molluscs from the Bento Gomes basin, although low, have shown that the mercury used in the gold mining activities in the Poconé wetlands has contaminated those aquatic habitats in Pantanal. From 69 sediment samples analyzed, 26 % (N = 18) have shown levels ranging from 0.01 to 0.25µg.g-1 of mercury (moist weight). Mercury levels analyzed in 54 samples of mollusc tissues (Ampullaria scalaris Orbigny, 1835; A. canaliculata Lamarck, 1819 and Marisa planogyra Pilsbry, 1933) have shown that 30% (N = 16) were contaminated with levels ranging from 0.02 to 1.16µg.g-1 moist weight. This study shows that the mercury used in digs for gold mining and released into the environment has reached the habitats of Pantanal spread from the sediment into the molluscs living in the region.